ANALYZING FEINBERG’S POETIC STYLE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Feinberg delves into the emotions, feelings of people  and often employs vivid imagery, metaphorical language, and rhythmic cadence to evoke profound emotional resonance.  Through his words, he  invites us to explore the depths of our own souls and find solace in the shared struggles and joys of being human